Silt and sand are opposite predictors of Amazonian palm distribution - Amaral, Márcio Rogério Mota; Spanner, Gustavo Carvalho; Gimenez, Bruno Oliva; Lima, Adriano José Nogueira; Santos, Joaquim dos; Higuchi, Niro; DeArmond, Daniel; Marra, Daniel Magnabosco (My University, 2025)
Palms (Arecaceae), although often overlooked in many forest inventories, hold significant ecological and functional importance within the Amazon biome. They are highly abundant and diverse, playing key roles in forest structure, providing trophic resources for wildlife, and contributing to the livelihoods of local populations. Here, we used data compiled from 1545 forest inventory plots, each measuring 0.25 ha. The objective was to evaluate the variation in density, relative abundance and basal area of arborescent palms (DBH ≥10 cm) on a regional scale (1500 km from west to east and 800 km from north to south) and their relationship with soil gradients (chemical and physical), climatic, Height Above the Nearest Drainage, and forest structure (tree density ≥ 50 cm). The independent variables were extracted from remote sensing data (forest structure data were obtained from the forest inventory),and the dependent variables were calculated from forest inventory data. Furthermore, we stratified the sampling points by Amazon Ecoregion to assess differences in relative abundance, basal area, and density of arborescent palms between ecoregions. Our results showed that palm tree stocking differs according to ecoregion. Moreover, the linear behavior varies according to the environmental variable and the different ecoregions analyzed. Among all the variables studied, soil physical variables, mainly silt content, were the ones that best explained the variation in relative abundance (R2m = 0.31), basal area (R2m = 0.34), and density (R2m = 0.29) of arborescent palms. This means that ecoregions with the highest silt content in the soil had the highest relative abundance, density and basal area of arborescent palms. Thus, understanding the relationship between soil properties and palms can inform forest management strategies, biodiversity conservation, and the sustainable utilization of Amazonian resources.
Keywords: Área Basal; Estrutura Florestal